A lithium battery negative electrode material and preparation method thereof
By preparing porous alloy oxides and surface modification and coating, the F/N/Si/P co-doped structure is formed, and the powdering problem caused by volume expansion of the negative electrode material of lithium ion batteries during the lithium ion embedding and disengagement process is solved. , improves the cycle life and first charge and discharge efficiency, and realizes high capacity and high efficiency of lithium-ion battery negative electrode materials.
Patent Information
- Application Number
- CN202311790435.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-25
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2043-12-25
AI Technical Summary
The existing lithium-ion battery negative electrode materials have volume expansion and contraction during the process of lithium ions embedded and disengagement, resulting in the powderization of the electrode material, affecting the circulation performance and life, and insufficient charging and discharging efficiency and capacity for the first time.
By preparing porous alloy oxides and modifying and coating them on their surfaces, a silane coupling agent and modified asphalt are used to form an F/N/Si/P co-doped structure to enhance the structure of the carbon cladding layer and Conductivity improves the absorption and diffusion rate of lithium ions and extends the cycle life.
It improves the electrochemical and mechanical properties of the negative electrode materials of lithium-ion batteries, extends the cycle life, improves the first charge and discharge efficiency and capacity, avoids the powdering of the electrode materials, and is suitable for continuous large-scale production.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a negative electrode material for a lithium battery and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have the advantages of high operating voltage, long service life, good safety performance, no memory effect, high energy density, stable discharge voltage, green and pollution-free, and short charging time. They have been widely used in portable electronic products and power tools, and are expected to become one of the main energy sources for hybrid vehicles and pure electric vehicles in the future. The negative electrode material is one of the key components of lithium batteries, which directly determines the cycle life and battery capacity of lithium batteries. It can be seen that it is particularly important to develop negative electrode materials with excellent comprehensive performance and performance stability.
[0003] The existing negative electrode materials for lithium-ion batteries mainly include: graphitized carbon materials, transition metal oxide materials and silicon materials. Graphitized carbon materials have poor compatibility with solvents and poor high-current charge and discharge performance. During the first charge and discharge, the co-embedding of solvent molecules causes the graphite layer to peel off and the structure to be damaged, which reduces the life of the electrode. Existing transition metal oxide materials will have large volume expansion and contraction changes during the process of lithium ion embedding and extraction, which will lead to the pulverization of the electrode material and then lose electrical contact with the current collector, greatly affecting the cycle performance and application of such materials. The volume expansion and poor conductivity of silicon materials themselves lead to pulverization during the material cycle, resulting in short life and poor cyclability during the lithium battery cycle.
[0004] In order to solve the above technical problems, the Chinese invention patent with the authorization announcement number CN108807921B discloses a method for preparing a negative electrode material for a lithium battery. First, a porous Fe-Sn-La-OBF preliminary product is prepared by a hydrothermal reaction, and then free radical polymerization occurs on the surface of the porous Fe-Sn-La-OBF preliminary product to form a polymer-modified porous Fe-Sn-La-OBF, and finally calcined at 450-550°C in a nitrogen atmosphere to obtain a Fe-Sn-La-OBF coated with a carbon layer co-doped with F / B / Si / P. The invention also discloses a lithium battery negative electrode material prepared according to the preparation method and a lithium battery using the negative electrode material as the negative electrode material. The lithium battery negative electrode material disclosed in the invention has low preparation price, high energy density, high battery capacity, long cycle life and good conductivity. However, it still has the phenomenon of negative electrode powder falling.
[0005] It can be seen that the art still needs a lithium battery negative electrode material with high specific capacity and initial charge and discharge efficiency and long cycle life and a preparation method thereof. Summary of the invention
[0006] The main purpose of the present invention is to provide a lithium battery negative electrode material with high specific capacity and initial charge and discharge efficiency and long cycle life and a preparation method thereof.
[0007] To achieve the above object, the present invention provides a method for preparing a negative electrode material for a lithium battery, comprising the following steps:
[0008] Step S1, preparation of porous alloy oxide: add cobalt source, rare earth source, silicon source and niobium source to an alcohol solvent, stir for 1-2 hours, slowly add sodium acetate, and then ultrasonically disperse for 1-4 hours, then transfer the dispersion to a hydrothermal reactor lined with polytetrafluoroethylene, react at 190-220° C. for 18-24 hours, cool the reactor to room temperature after the reaction, centrifuge to separate the precipitate, wash with ethanol 3-6 times, filter, and finally dry the obtained sample in a vacuum drying oven at 80-90° C. to constant weight, and then heat treat at 550-650° C. in a nitrogen atmosphere for 5-8 hours to obtain a porous alloy oxide;
[0009] Step S2, surface modification: the porous alloy oxide prepared in step S1 is uniformly dispersed in a high boiling point solvent, and then a silane coupling agent KH560 and bis(3-aminophenyl)3,5-bis(trifluoromethyl)phenylphosphine oxide are added, and the mixture is stirred at 70-80° C. for 5-8 hours, and then the solvent is removed by rotary evaporation to obtain a surface-modified porous alloy oxide;
[0010] Step S3, preparation of modified asphalt: adding coal tar pitch, bis(1-vinyl imidazole-2-one)ketone and a catalyst into a three-necked flask, heating to 120-145° C. at a rate of 5-8° C. / min under an inert gas atmosphere, and stirring for 3-6 hours to obtain modified asphalt;
[0011] Step S4, surface coating: the surface-modified porous alloy oxide prepared in step S2 is placed in a stirring coating device, and heated at 180-210° C. for 1-2 hours by stirring, and then the modified asphalt prepared in step S3 is heated to 180-210° C., and sprayed onto the surface-modified porous alloy oxide being stirred with a spray gun, and after spraying, the surface is continuously stirred at a constant temperature for 1-2 hours to complete the coating;
[0012] Step S5, calcination: under the protection of nitrogen, the temperature is raised to 700-900° C. at a rate of 3-6° C. / min and calcined for 3-6 hours.
[0013] Preferably, in step S1, the cobalt source is at least one of cobalt chloride and cobalt nitrate; the rare earth source is at least one of scandium nitrate and yttrium nitrate; the silicon source is silicon tetrachloride; and the niobium source is niobium pentachloride.
[0014] Preferably, the alcohol solvent is at least one of ethanol, glycerol and ethylene glycol.
[0015] Preferably, the mass ratio of the cobalt source, rare earth source, silicon source, niobium source, alcohol solvent and sodium acetate is 1:(0.1-0.3):(1-2):0.2:(15-25):8.
[0016] Preferably, in step S2, the mass ratio of the porous alloy oxide, the high boiling point solvent, the silane coupling agent KH560, and bis(3-aminophenyl)3,5-bis(trifluoromethyl)phenylphosphine oxide is (4-6):(10-25):1.1:1.
[0017] Preferably, the high boiling point solvent is at least one of dimethyl sulfoxide, N,N-dimethylformamide and N-methylpyrrolidone.
[0018] Preferably, the catalyst in step S3 is p-toluenesulfonic acid; the mass ratio of the coal tar pitch, bis(1-vinylimidazole-2-)ketone, and the catalyst is (3-5):1:0.5.
[0019] Preferably, the mass ratio of the surface-modified porous alloy oxide to the modified asphalt in step S4 is (6-8):1.
[0020] Preferably, the inert gas in step S4 is at least one of nitrogen, helium, neon and argon.
[0021] Another object of the present invention is to provide a lithium battery negative electrode material prepared by the above-mentioned method for preparing a lithium battery negative electrode material.
[0022] Due to the application of the above technical solution, the present invention has the following beneficial effects:
[0023] (1) The method for preparing the negative electrode material for lithium batteries disclosed in the present invention is simple, efficient, has a short process flow, is easy to operate and control, has low dependence on equipment, and is suitable for continuous large-scale production.
[0024] (2) The lithium battery negative electrode material disclosed in the present invention, through the rational re-selection of the components in the porous alloy oxide, makes the prepared oxide contain cobalt, rare earth, silicon and niobium at the same time. The cooperation between them can effectively improve its electrochemical performance, enhance its mechanical properties and performance stability, and thus ensure the integrity of the material structure during the process of lithium ion insertion and extraction.
[0025] (3) The surface modification and coating of the lithium battery negative electrode material disclosed in the present invention can simultaneously introduce the F / N / Si / P / S co-doping structure. By rationally selecting the modified raw materials and their content ratios, the structure of the carbon coating layer can be improved, thereby enhancing its absorption of lithium ions, improving conductivity, and accelerating the diffusion rate of lithium ions between electrode materials, thereby extending the cycle life and improving the specific capacity and initial charge and discharge efficiency.
[0026] (4) The lithium battery negative electrode material disclosed in the present invention is first surface-modified, and an epoxy ring-opening reaction occurs between the silane coupling agent KH560 and the epoxy group in its molecular structure and the amino group on bis(3-aminophenyl)3,5-bis(trifluoromethyl)phenylphosphine oxide to form a transition layer on the surface of the alloy oxide, and then the modified asphalt is used for coating, which can enhance the structural stability and improve the electrochemical activity; the coal tar is modified to introduce an imidazolide structure into the molecular structure, thereby improving the uniformity of N doping and adjusting the N doping ratio in the coated carbon layer, thereby improving the electrochemical activity and cycle life of the negative electrode material product; at the same time, through such a modified coating structure design, the structural stability can also be improved, avoiding the pulverization of the electrode material caused by large volume expansion and contraction changes during the insertion and extraction of lithium ions. DETAILED DESCRIPTION
[0027] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations. Example 1
[0028] A method for preparing a negative electrode material for a lithium battery comprises the following steps:
[0029] Step S1, preparation of porous alloy oxide: add cobalt source, rare earth source, silicon source and niobium source to an alcohol solvent, stir for 1 hour, slowly add sodium acetate, and then ultrasonically disperse for 1 hour, then transfer the dispersion to a hydrothermal reactor lined with polytetrafluoroethylene, react at 190°C for 18 hours, cool the reactor to room temperature after the reaction, centrifuge to separate the precipitate, wash with ethanol 3 times, filter, and finally dry the obtained sample in a vacuum drying oven at 80°C to constant weight, and then heat treat at 550°C in a nitrogen atmosphere for 5 hours to obtain a porous alloy oxide;
[0030] Step S2, surface modification: the porous alloy oxide prepared in step S1 is uniformly dispersed in a high boiling point solvent, and then a silane coupling agent KH560 and bis(3-aminophenyl)3,5-bis(trifluoromethyl)phenylphosphine oxide are added, and the mixture is stirred at 70° C. for 5 hours, and then the solvent is removed by rotary evaporation to obtain a surface-modified porous alloy oxide;
[0031] Step S3, preparation of modified asphalt: coal tar pitch, bis(1-vinyl imidazole-2-one)ketone and a catalyst are added into a three-necked flask, heated to 120° C. at a rate of 5° C. / min under an inert gas atmosphere, and stirred for 3 hours to obtain modified asphalt;
[0032] Step S4, surface coating: the surface-modified porous alloy oxide prepared in step S2 is placed in a stirring coating device, and heated at 180° C. for 1 h under stirring, and then the modified asphalt prepared in step S3 is heated to 180° C. and sprayed onto the surface-modified porous alloy oxide being stirred with a spray gun. After spraying, the surface is stirred at a constant temperature for 1 h to complete the coating;
[0033] Step S5, calcination: under the protection of nitrogen, the temperature was raised to 700° C. at a rate of 3° C. / min and calcined for 3 h.
[0034] In step S1, the cobalt source is cobalt chloride; the rare earth source is scandium nitrate; the silicon source is silicon tetrachloride; the niobium source is niobium pentachloride; the alcohol solvent is ethanol; and the mass ratio of the cobalt source, rare earth source, silicon source, niobium source, alcohol solvent, and sodium acetate is 1:0.1:1:0.2:15:8.
[0035] The mass ratio of the porous alloy oxide, the high boiling point solvent, the silane coupling agent KH560, and the bis(3-aminophenyl)3,5-bis(trifluoromethyl)phenylphosphine oxide in step S2 is 4:10:1.1:1; the high boiling point solvent is dimethyl sulfoxide; the catalyst in step S3 is p-toluenesulfonic acid; the mass ratio of the coal tar, bis(1-vinylimidazole-2-)ketone, and the catalyst is 3:1:0.5.
[0036] The mass ratio of the surface-modified porous alloy oxide to the modified asphalt in step S4 is 6:1; and the inert gas in step S4 is nitrogen.
[0037] A negative electrode material for a lithium battery prepared by using the above-mentioned method for preparing a negative electrode material for a lithium battery. Example 2
[0038] A method for preparing a negative electrode material for a lithium battery comprises the following steps:
[0039] Step S1, preparation of porous alloy oxide: add cobalt source, rare earth source, silicon source and niobium source to alcohol solvent, stir for 1.2 hours, slowly add sodium acetate, and then ultrasonically disperse for 2 hours, then transfer the dispersion to a hydrothermal reactor lined with polytetrafluoroethylene, react at 200°C for 19 hours, cool the reactor to room temperature after the reaction, centrifuge to separate the precipitate, wash with ethanol 4 times, filter, and finally dry the obtained sample in a vacuum drying oven at 83°C to constant weight, and then heat treat at 570°C in a nitrogen atmosphere for 6 hours to obtain a porous alloy oxide;
[0040] Step S2, surface modification: the porous alloy oxide prepared in step S1 is uniformly dispersed in a high boiling point solvent, and then a silane coupling agent KH560 and bis(3-aminophenyl)3,5-bis(trifluoromethyl)phenylphosphine oxide are added, and the mixture is stirred and reacted at 73° C. for 6 hours, and then the solvent is removed by rotary evaporation to obtain a surface-modified porous alloy oxide;
[0041] Step S3, preparation of modified asphalt: coal tar pitch, bis(1-vinyl imidazole-2-one)ketone and a catalyst are added into a three-necked flask, heated to 125° C. at a rate of 6° C. / min under an inert gas atmosphere, and stirred for 4 hours to obtain modified asphalt;
[0042] Step S4, surface coating: the surface-modified porous alloy oxide prepared in step S2 is placed in a stirring coating device, and heated at 190° C. for 1.2 h with stirring, and then the modified asphalt prepared in step S3 is heated to 190° C. and sprayed onto the surface-modified porous alloy oxide being stirred with a spray gun. After spraying, the surface is stirred at a constant temperature for 1.2 h to complete the coating;
[0043] Step S5, calcination: under the protection of nitrogen, the temperature was raised to 750° C. at 4° C. / min and calcined for 4 h.
[0044] In step S1, the cobalt source is cobalt nitrate; the rare earth source is yttrium nitrate; the silicon source is silicon tetrachloride; the niobium source is niobium pentachloride; the alcohol solvent is propylene glycol; and the mass ratio of the cobalt source, rare earth source, silicon source, niobium source, alcohol solvent, and sodium acetate is 1:0.15:1.2:0.2:17:8.
[0045] In step S2, the mass ratio of the porous alloy oxide, the high boiling point solvent, the silane coupling agent KH560, and bis(3-aminophenyl)3,5-bis(trifluoromethyl)phenylphosphine oxide is 4.5:13:1.1:1; and the high boiling point solvent is N,N-dimethylformamide.
[0046] The catalyst in step S3 is p-toluenesulfonic acid; the mass ratio of the coal tar pitch, bis(1-vinylimidazole-2-)ketone and the catalyst is 3.5:1:0.5; the mass ratio of the surface-modified porous alloy oxide and the modified asphalt in step S4 is 6.5:1; the inert gas in step S4 is helium.
[0047] A negative electrode material for a lithium battery prepared by using the above-mentioned method for preparing a negative electrode material for a lithium battery. Example 3
[0048] A method for preparing a negative electrode material for a lithium battery comprises the following steps:
[0049] Step S1, preparation of porous alloy oxide: add cobalt source, rare earth source, silicon source and niobium source to alcohol solvent, stir for 1.5 hours, slowly add sodium acetate, and then ultrasonically disperse for 2.5 hours, then transfer the dispersion to a hydrothermal reactor lined with polytetrafluoroethylene, react at 205°C for 21 hours, cool the reactor to room temperature after the reaction, centrifuge to separate the precipitate, wash with ethanol 5 times, filter, and finally dry the obtained sample in a vacuum drying oven at 85°C to constant weight, and then heat treat at 600°C in a nitrogen atmosphere for 6.5 hours to obtain a porous alloy oxide;
[0050] Step S2, surface modification: the porous alloy oxide prepared in step S1 is uniformly dispersed in a high boiling point solvent, and then a silane coupling agent KH560 and bis(3-aminophenyl)3,5-bis(trifluoromethyl)phenylphosphine oxide are added, and the mixture is stirred at 75° C. for 6.5 hours, and then the solvent is removed by rotary evaporation to obtain a surface-modified porous alloy oxide;
[0051] Step S3, preparation of modified asphalt: coal tar pitch, bis(1-vinyl imidazole-2-one)ketone and a catalyst are added into a three-necked flask, heated to 135° C. at a rate of 6.5° C. / min under an inert gas atmosphere, and stirred for 5 hours to obtain modified asphalt;
[0052] Step S4, surface coating: the surface-modified porous alloy oxide prepared in step S2 is placed in a stirring coating device, and heated at 195° C. for 1.5 h with stirring, and then the modified asphalt prepared in step S3 is heated to 200° C. and sprayed onto the surface-modified porous alloy oxide being stirred with a spray gun. After spraying, the surface-modified porous alloy oxide is stirred at a constant temperature for 1.5 h to complete the coating;
[0053] Step S5, calcination: under the protection of nitrogen, the temperature was raised to 800° C. at a rate of 4.5° C. / min and calcined for 4.5 h.
[0054] In step S1, the cobalt source is cobalt chloride; the rare earth source is yttrium nitrate; the silicon source is silicon tetrachloride; the niobium source is niobium pentachloride; the alcohol solvent is ethylene glycol; and the mass ratio of the cobalt source, rare earth source, silicon source, niobium source, alcohol solvent, and sodium acetate is 1:0.2:1.5:0.2:20:8.
[0055] The mass ratio of the porous alloy oxide, the high boiling point solvent, the silane coupling agent KH560, and the bis(3-aminophenyl)3,5-bis(trifluoromethyl)phenylphosphine oxide in step S2 is 5:19:1.1:1; the high boiling point solvent is N-methylpyrrolidone; the catalyst in step S3 is p-toluenesulfonic acid; the mass ratio of the coal tar, bis(1-vinylimidazole-2-)ketone, and the catalyst is 4:1:0.5.
[0056] The mass ratio of the surface-modified porous alloy oxide to the modified asphalt in step S4 is 7:1; the inert gas in step S4 is neon.
[0057] A negative electrode material for a lithium battery prepared by using the above-mentioned method for preparing a negative electrode material for a lithium battery. Example 4
[0058] A method for preparing a negative electrode material for a lithium battery comprises the following steps:
[0059] Step S1, preparation of porous alloy oxide: add cobalt source, rare earth source, silicon source and niobium source to alcohol solvent, stir for 1.8 hours, slowly add sodium acetate, and then ultrasonically disperse for 3.5 hours, then transfer the dispersion to a hydrothermal reactor lined with polytetrafluoroethylene, react at 215°C for 23 hours, cool the reactor to room temperature after the reaction, centrifuge to separate the precipitate, wash with ethanol 6 times, filter, and finally dry the obtained sample in a vacuum drying oven at 88°C to constant weight, and then heat treat at 640°C in a nitrogen atmosphere for 7.5 hours to obtain a porous alloy oxide;
[0060] Step S2, surface modification: the porous alloy oxide prepared in step S1 is uniformly dispersed in a high boiling point solvent, and then a silane coupling agent KH560 and bis(3-aminophenyl)3,5-bis(trifluoromethyl)phenylphosphine oxide are added, and the mixture is stirred at 78° C. for 7.5 hours, and then the solvent is removed by rotary evaporation to obtain a surface-modified porous alloy oxide;
[0061] Step S3, preparation of modified asphalt: coal tar pitch, bis(1-vinyl imidazole-2-one)ketone and a catalyst are added into a three-necked flask, heated to 142° C. at a rate of 7.5° C. / min under an inert gas atmosphere, and stirred for 5.5 hours to obtain modified asphalt;
[0062] Step S4, surface coating: the surface-modified porous alloy oxide prepared in step S2 is placed in a stirring coating device, and heated at 205° C. for 1.8 h under stirring, and then the modified asphalt prepared in step S3 is heated to 205° C. and sprayed onto the surface-modified porous alloy oxide being stirred with a spray gun. After spraying, the surface is stirred at a constant temperature for 1.8 h to complete the coating;
[0063] Step S5, calcination: under the protection of nitrogen, the temperature was raised to 850° C. at 5.5° C. / min and calcined for 5 h.
[0064] In step S1, the cobalt source is a mixture of cobalt chloride and cobalt nitrate in a mass ratio of 3:5; the rare earth source is a mixture of scandium nitrate and yttrium nitrate in a mass ratio of 1:3; the silicon source is silicon tetrachloride; the niobium source is niobium pentachloride; the alcohol solvent is a mixture of ethanol, propylene glycol and ethylene glycol in a mass ratio of 1:1:2; the mass ratio of the cobalt source, rare earth source, silicon source, niobium source, alcohol solvent and sodium acetate is 1:0.25:1.8:0.2:23:8.
[0065] The mass ratio of the porous alloy oxide, the high boiling point solvent, the silane coupling agent KH560, and the bis(3-aminophenyl)3,5-bis(trifluoromethyl)phenylphosphine oxide in step S2 is 5.5:23:1.1:1; the high boiling point solvent is a mixture of dimethyl sulfoxide, N,N-dimethylformamide, and N-methylpyrrolidone in a mass ratio of 1:3:2; the catalyst in step S3 is p-toluenesulfonic acid; the mass ratio of the coal tar, bis(1-vinylimidazole-2-)ketone, and the catalyst is 4.5:1:0.5.
[0066] The mass ratio of the surface-modified porous alloy oxide to the modified asphalt in step S4 is 7.5:1; and the inert gas in step S4 is nitrogen.
[0067] A negative electrode material for a lithium battery prepared by using the above-mentioned method for preparing a negative electrode material for a lithium battery. Example 5
[0068] A method for preparing a negative electrode material for a lithium battery comprises the following steps:
[0069] Step S1, preparation of porous alloy oxide: add cobalt source, rare earth source, silicon source and niobium source to an alcohol solvent, stir for 2 hours, slowly add sodium acetate, and then ultrasonically disperse for 4 hours, then transfer the dispersion to a hydrothermal reactor lined with polytetrafluoroethylene, react at 220°C for 24 hours, cool the reactor to room temperature after the reaction, centrifuge to separate the precipitate, wash with ethanol 6 times, filter, and finally dry the obtained sample in a vacuum drying oven at 90°C to constant weight, and then heat treat at 650°C in a nitrogen atmosphere for 8 hours to obtain a porous alloy oxide;
[0070] Step S2, surface modification: the porous alloy oxide prepared in step S1 is uniformly dispersed in a high boiling point solvent, and then a silane coupling agent KH560 and bis(3-aminophenyl)3,5-bis(trifluoromethyl)phenylphosphine oxide are added, and the mixture is stirred and reacted at 80° C. for 8 hours, and then the solvent is removed by rotary evaporation to obtain a surface-modified porous alloy oxide;
[0071] Step S3, preparation of modified asphalt: coal tar pitch, bis(1-vinyl imidazole-2-one)ketone and a catalyst are added into a three-necked flask, heated to 145° C. at a rate of 8° C. / min under an inert gas atmosphere, and stirred for 6 hours to obtain modified asphalt;
[0072] Step S4, surface coating: the surface-modified porous alloy oxide prepared in step S2 is placed in a stirring coating device, and stirred and heated at 210° C. for 2 h. Then, the modified asphalt prepared in step S3 is heated to 210° C. and sprayed onto the surface-modified porous alloy oxide being stirred with a spray gun. After spraying, the surface is stirred at a constant temperature for 2 h to complete the coating.
[0073] Step S5, calcination: under the protection of nitrogen, the temperature was raised to 900° C. at 6° C. / min and calcined for 6 h.
[0074] In step S1, the cobalt source is cobalt nitrate; the rare earth source is scandium nitrate; the silicon source is silicon tetrachloride; the niobium source is niobium pentachloride; the alcohol solvent is ethylene glycol; and the mass ratio of the cobalt source, rare earth source, silicon source, niobium source, alcohol solvent, and sodium acetate is 1:0.3:2:0.2:25:8.
[0075] The mass ratio of the porous alloy oxide, the high boiling point solvent, the silane coupling agent KH560, and the bis(3-aminophenyl)3,5-bis(trifluoromethyl)phenylphosphine oxide in step S2 is 6:25:1.1:1; the high boiling point solvent is dimethyl sulfoxide; the catalyst in step S3 is p-toluenesulfonic acid; the mass ratio of the coal tar, bis(1-vinylimidazole-2-)ketone, and the catalyst is 5:1:0.5.
[0076] The mass ratio of the surface-modified porous alloy oxide to the modified asphalt in step S4 is 8:1; and the inert gas in step S4 is nitrogen.
[0077] A negative electrode material for a lithium battery prepared by using the above-mentioned method for preparing a negative electrode material for a lithium battery.
[0078] Comparative Example 1
[0079] A lithium battery negative electrode material and a preparation method thereof, which are substantially the same as those in Example 1, except that no cobalt source, niobium source and bis(3-aminophenyl)3,5-bis(trifluoromethyl)phenylphosphine oxide are added.
[0080] Comparative Example 2
[0081] A lithium battery negative electrode material and a preparation method thereof, which are substantially the same as those in Example 1, except that no rare earth source and bis(1-vinylimidazole-2-)ketone are added.
[0082] In order to further illustrate the beneficial technical effects of the negative electrode materials of lithium batteries in various embodiments of the present invention, the negative electrode materials of lithium batteries prepared in Examples 1-5 and Comparative Examples 1-2 were subjected to relevant performance tests. The test results are shown in Table 1. The test method is as follows: the negative electrode materials of Examples 1-5 and Comparative Examples 1-2, the conductive agent SP, the thickener CMC, and the binder SBR were mixed in a mass ratio of 94:1:1.5:3.5, and an appropriate amount of deionized water was added as a dispersant to prepare a slurry, which was then coated on a copper foil, and vacuum dried and rolled to prepare a negative electrode sheet. Metal lithium was used as the counter electrode, and 1 mol / L of The electrolyte of LiPF6 three-component mixed solvent (EC, DMC, EMC mixed in a volume ratio of 1:1:1) was used, and a polypropylene microporous membrane was used as a separator. The button cell was assembled into a CR2016 type button cell in a glove box filled with argon. The button cell was charged and discharged in the Neware battery test system of Shenzhen Neware Co., Ltd. The test conditions were: at room temperature, 0.1C constant current charge and discharge, the charge and discharge voltage was limited to 0.005~1.5V, and the long cycle test was 0.5C charging and 1C discharging, and the charge and discharge voltage was limited to 0.005~1.5V. The test results are shown in Table 1:
[0083] Table 1
[0084]
[0085] It can be seen from Table 1 that the negative electrode materials for lithium batteries disclosed in the embodiments of the present invention have better electrochemical performance and cycle life than the comparative example method; the addition of cobalt source, niobium source, bis(3-aminophenyl)3,5-bis(trifluoromethyl)phenylphosphine oxide, rare earth source and bis(1-vinylimidazole-2-)ketone is beneficial to improving the above performance.
[0086] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a negative electrode material for a lithium battery, characterized in that: The steps include: Step S1, preparation of porous alloy oxide: add cobalt source, rare earth source, silicon source and niobium source to an alcohol solvent, stir for 1-2 hours, slowly add sodium acetate, and then ultrasonically disperse for 1-4 hours, then transfer the dispersion to a hydrothermal reactor lined with polytetrafluoroethylene, react at 190-220° C. for 18-24 hours, cool the reactor to room temperature after the reaction, centrifuge to separate the precipitate, wash with ethanol 3-6 times, filter, and finally dry the obtained sample in a vacuum drying oven at 80-90° C. to constant weight, and then heat treat at 550-650° C. in a nitrogen atmosphere for 5-8 hours to obtain a porous alloy oxide; Step S2, surface modification: the porous alloy oxide prepared in step S1 is uniformly dispersed in a high boiling point solvent, and then a silane coupling agent KH560 and bis(3-aminophenyl)3,5-bis(trifluoromethyl)phenylphosphine oxide are added, and the mixture is stirred at 70-80° C. for 5-8 hours, and then the solvent is removed by rotary evaporation to obtain a surface-modified porous alloy oxide; Step S3, preparation of modified asphalt: adding coal tar pitch, bis(1-vinyl imidazole-2-one)ketone and a catalyst into a three-necked flask, heating to 120-145° C. at a rate of 5-8° C. / min under an inert gas atmosphere, and stirring for 3-6 hours to obtain modified asphalt; Step S4, surface coating: the surface-modified porous alloy oxide prepared in step S2 is placed in a stirring coating device, and heated at 180-210° C. for 1-2 hours by stirring, and then the modified asphalt prepared in step S3 is heated to 180-210° C., and sprayed onto the surface-modified porous alloy oxide being stirred with a spray gun, and after spraying, the surface is continuously stirred at a constant temperature for 1-2 hours to complete the coating; Step S5, calcination: under the protection of nitrogen, the temperature is raised to 700-900° C. at a rate of 3-6° C. / min and calcined for 3-6 hours.
2. The method for preparing a negative electrode material for a lithium battery according to claim 1, characterized in that: In step S1, the cobalt source is at least one of cobalt chloride and cobalt nitrate; the rare earth source is at least one of scandium nitrate and yttrium nitrate; the silicon source is silicon tetrachloride; and the niobium source is niobium pentachloride.
3. The method for preparing a negative electrode material for a lithium battery according to claim 1, characterized in that: The alcohol solvent is at least one of ethanol, glycerol and ethylene glycol.
4. The method for preparing a negative electrode material for a lithium battery according to claim 1, characterized in that: The mass ratio of the cobalt source, rare earth source, silicon source, niobium source, alcohol solvent and sodium acetate is 1:(0.1-0.3):(1-2):0.2:(15-25):
8.
5. The method for preparing a negative electrode material for a lithium battery according to claim 1, characterized in that: The mass ratio of the porous alloy oxide, the high boiling point solvent, the silane coupling agent KH560, and bis(3-aminophenyl)3,5-bis(trifluoromethyl)phenylphosphine oxide in step S2 is (4-6):(10-25):1.1:
1.
6. The method for preparing a negative electrode material for a lithium battery according to claim 1, characterized in that: The high boiling point solvent is at least one of dimethyl sulfoxide, N,N-dimethylformamide and N-methylpyrrolidone.
7. The method for preparing a negative electrode material for a lithium battery according to claim 1, characterized in that: The catalyst in step S3 is p-toluenesulfonic acid; the mass ratio of the coal tar pitch, bis(1-vinylimidazole-2-)ketone and the catalyst is (3-5):1:0.
5.
8. The method for preparing a negative electrode material for a lithium battery according to claim 1, characterized in that: The mass ratio of the surface-modified porous alloy oxide to the modified asphalt in step S4 is (6-8):
1.
9. The method for preparing a negative electrode material for a lithium battery according to claim 1, characterized in that: The inert gas atmosphere in step S3 is at least one of nitrogen, helium, neon and argon.
10. A negative electrode material for a lithium battery prepared by the method for preparing a negative electrode material for a lithium battery according to any one of claims 1 to 9.
